Impact of Operating Cost Reduction on The Economic Challenges Facing Small-Size Clothing Factories in Saudi Arabia - aldaady, sarah; Basafar, Amal (Advances in Social Sciences Research Journal, 2020)
The clothing manufacturing industry in the Kingdom of Saudi Arabia has faced many challenges at the local and international level. The implementation of the rules and regulations of the World Trade Organization (WTO) and the Kingdom’s Vision 2030 have gained particular interest and operating with minimum costs has become one of the main objectives of small-size clothing factories. The impact of operating cost reduction on economic challenges facing the clothing factories has been studied with the aim to identify the challenges and economic factors affecting operating costs. It was concluded that some of the economic challenges are represented in the high operating cost caused by the application of new taxes, including the value-added tax (VAT), imposition of fees on non-Saudi workers and new amendments to the trade law. Minimizing operating costs through cutting-edge manufacturing technologies were found to be a key solution to ensure factories’ survival and sustainability.